Examining the accuracy of trackways for predicting gait selection and speed of locomotion - Marmol-Guijarro, Andres; Nudds, Robert; Folkow, Lars; Codd, Jonathan (Frontiers in Zoology, 2020)
Using Froude numbers ( Fr ) and relative stride length (stride length: hip height), trackways have been widely used to determine the speed and gait of an animal. This approach, however, is limited by the ability to estimate hip height accurately and by the lack of information related to the substrate properties when the tracks were made, in particular for extinct fauna. By studying the Svalbard ptarmigan moving on snow, we assessed the accuracy of trackway predictions from a species-specific model and two additional Fr based models by ground truthing data extracted from videos as the tracks were being made.